1998
DOI: 10.1111/j.1475-2743.1998.tb00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of nitrate leaching from a Nitrate Vulnerable Zone using paper mill waste

Abstract: Abstract.The effects on nitrate leaching of incorporation of paper mill waste at three cultivation depths in fields previously cropped to iceberg lettuce and calabrese are reported. In the lettuce experiment, incorporation of 40 t DM paper mill wasteiha resulted in a decrease in N leaching (measured with suction cups) from 177 to 94 kgiha (S.Ed=23). Deep ploughing with and without paper waste increased N leaching from 105 kgiha (normal ploughing or surface incorporation) to 172 kgiha (S.E.d = 27). Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
4
32
0
Order By: Relevance
“…Wheat straw was more effective at immobilizing N than the mineral ®bre in spite of a narrower C : N ratio. These observations support the views of Vinten et al (1998) that C : N ratios of amendment materials alone are not suf®cient to predict immobilizing capacity accurately. In our experiments and those reported above, C was evidently still in an available form to support the growth of micro-organisms in materials with very wide C : N ratios, such as compactor waste.…”
Section: Characteristics Of the Waste Materialssupporting
confidence: 83%
See 2 more Smart Citations
“…Wheat straw was more effective at immobilizing N than the mineral ®bre in spite of a narrower C : N ratio. These observations support the views of Vinten et al (1998) that C : N ratios of amendment materials alone are not suf®cient to predict immobilizing capacity accurately. In our experiments and those reported above, C was evidently still in an available form to support the growth of micro-organisms in materials with very wide C : N ratios, such as compactor waste.…”
Section: Characteristics Of the Waste Materialssupporting
confidence: 83%
“…Recent ®eld studies have suggested that short-term rates of N mineralization and subsequent NO 3 ± leaching can be minimized by the incorporation of paper waste along with crop residues (Vinten et al 1998). These results demonstrated that there is scope to develop novel strategies for crop residue management based on the addition of substrates to in¯uence directly the activities of the decomposer organisms.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Agricultural activities such as cattle farming can have a significant impact on nitrate (NO − 3 ) leaching and groundwater pollution (Ball et al, 1979;Field et al, for microbial denitrification and/or N immobilization or by increasing the presence of anaerobic microsites (due to soil pore blocking from solids of DE or increased microbial activity), which favors denitrification (Parkin, 1987;Aulakh et al, 1992;Hojberg et al, 1994;Paul and Clark, 1996;Drury et al, 1998;Vinten et al, 1998Vinten et al, , 2002. Contrary, compared to DE, urea applied to grazed pasture does not markedly change the soil C content or moisture.…”
Section: Introductionmentioning
confidence: 98%
“…The soil sink of nitrogen is related to immobilization mechanisms, which also remains poorly understood (TorresCañabate et al 2008), and may be associated with the presence of organic matter and biotic and abiotic immobilization (Vinten et al 1998;Torres-Cañabate et al 2008). Therefore, the addition of organic wastes and the use of inorganic residues for soil rehabilitation and quarry restoration can affect or control the nitrogen leaching into the nitrate vulnerable zone for waters (Vinten et al 1998;Jordán et al 2006;Santibánez et al 2007).…”
Section: Introductionmentioning
confidence: 97%